Dental caries experience of 12 year old children from Resen municipality - Nonkulovski Zoran; Ambarkova Vesna; Jankulovska Mira; Krmzova Tina; Arjeta Sulejmani; Violeta Nonkulovska (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Introduction: Despite scientific advances and the fact that caries is preventable, dental caries are still the most prevalent dental affliction of childhood within developing countries. Aims: The aim of this study was to assess dental caries in 12-year-old children from Resen municipality suited at the Pelagonia region of the Republic of North Macedonia.  Methods: In this cross-sectional study, primary school children from sixth grades (N=158 ) were selected from (5) primary schools from the Resen municipality. The Dental status of the children was evaluated during 2020 year, using the 2013 World Health Organization caries diagnostic criteria for Decayed, Missing and Filled Teeth (DMFT) by 2 calibrated examiners. Data obtained during the survey was stored in a database and statistical analysis with SPSS v.21(IBM). Using the t-test, the data were tested for possible statistically significant differences. A p value< 0.05 was considered statistically significant. Parental consent was obtained for each child. Results: The total number of children (N=158) in the sample was comprising 71(44.94% ) females and 87(55,06%) males. The mean DMFT score of the whole sample was 1.82±1.82. The average DMFT score within female children was 1.70±2.03, while within male children was 1.92±1.64. The average DMFT score within children from urban area was 1.71±1.65, while within children from rural area was 1.94±1.98. The prevalence of caries free children was 36.08%. Conclusion: Тhe prevalence of dental caries within 12-year-old children from the Resen municipality and its surrounding was 63.92%.